ENGLISH PROFICIENCY, PUBLIC SPEAKING EXPERIENCE, AND COMMUNICATION APPREHENSION IN ORAL PRESENTATION OF POLYTECHNIC STUDENTS - Marcus Gee-Whai Kho; Su-Hie Ting (Leksema: Jurnal Bahasa dan Sastra, 2023)
Oral presentation apprehension plagues people when they communicate orally, especially when they make oral presentations in public.  This study examined the relationship between English proficiency, public speaking experience, and communication apprehension in polytechnic students during oral presentations.  The study involved 62 students from a polytechnic in Sarawak, Malaysia, who filled in the PRCA-24 questionnaire that focused on the elements of public speaking.  The results showed that 6.4% of the students had a low level of communication apprehension, while 71% had a moderate level of communication apprehension.  For 22.6% of the students, the level of apprehension was very high.  The students felt anxious and uncomfortable when asked to give an oral presentation.  The t-test showed that the male students significantly differed from the female students regarding their communication apprehension.  The mean scores showed that the male students experienced greater communication apprehension (M= 2.19 ± 0.52) than the female students (M= 2.00 ± 0.44).  There was a significant negative relationship between oral presentation experience and the level of communication apprehension.  These results may suggest that extensive training in public speaking can improve public speaking skills and enhance employability opportunities.